2022
DOI: 10.1155/2022/7307078
|View full text |Cite
|
Sign up to set email alerts
|

Post-Veraison Water Stress and Pruning Level on Merlot Grapevine (Vitis vinifera L.): Effects on Berry Development and Composition

Abstract: The grapevine berry development and composition at harvest are major determinant of productivity and wine quality. The increase in grapevine productivity by applying proper pruning and watering may affect fruit traits of the grapevine development notably berry size, weight, and volume as well as the berry composition mainly the total soluble solids (TSSs), titratable acidity (TA), pH of the grapes, total anthocyanins, and phenolic content and concentration. In this context, this study aimed to explore the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 42 publications
(72 reference statements)
0
1
0
Order By: Relevance
“…In fact, it was demonstrated that water stress (deficit threshold, more than 50% of ETc-evapotranspiration during the bud break and bloom step) can reduce the yield [ 34 ]. Furthermore, water scarcity, depending on the level and period, can also affect the technological composition of the berries [ 35 , 36 , 37 ]. From the point of view of sugars, two distinct scenarios open up: on the one hand, a possible accumulation due to concentration was found [ 38 ], and on the other, in prolonged periods there was an inhibition due to the sudden decrease in photosynthesis, with the consequent arrest or slowing of maturation [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it was demonstrated that water stress (deficit threshold, more than 50% of ETc-evapotranspiration during the bud break and bloom step) can reduce the yield [ 34 ]. Furthermore, water scarcity, depending on the level and period, can also affect the technological composition of the berries [ 35 , 36 , 37 ]. From the point of view of sugars, two distinct scenarios open up: on the one hand, a possible accumulation due to concentration was found [ 38 ], and on the other, in prolonged periods there was an inhibition due to the sudden decrease in photosynthesis, with the consequent arrest or slowing of maturation [ 39 ].…”
Section: Introductionmentioning
confidence: 99%